2021
DOI: 10.1136/bmjopen-2020-045515
|View full text |Cite
|
Sign up to set email alerts
|

Open organisational culture: what does it entail? Healthcare stakeholders reaching consensus by means of a Delphi technique

Abstract: ObjectivesOpen organisational culture in hospitals is important, yet it remains unclear what it entails other than its referral to ‘open communication’ in the context of patient safety. This study aims to identify the elements of an open hospital culture.MethodsIn this group consensus study with a Delphi technique, statements were constructed based on the existing patient safety literature and input of 11 healthcare professionals from different backgrounds. A final framework consisting of 36 statements was rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…By placing the clerks in the role of medical coaches and giving them the task of briefing and debriefing patients before and after a consultation with a physician, the MedGezel initiative risked upgrading the status of the clerk and making the physician an object of potential criticism, which would conflict with a well-studied subject in medical culture, i.e., ‘saving face’ [ 34 ]. Physician culture dictates that openly criticizing each other is to be avoided, whereas an open culture is needed to be able to discuss each other’s performance [ 35 ]. Studies of Witman [ 36 ] and Scheepers [ 37 ] in the Netherlands revealed flaws in the achievement of an open culture.…”
Section: Resultsmentioning
confidence: 99%
“…By placing the clerks in the role of medical coaches and giving them the task of briefing and debriefing patients before and after a consultation with a physician, the MedGezel initiative risked upgrading the status of the clerk and making the physician an object of potential criticism, which would conflict with a well-studied subject in medical culture, i.e., ‘saving face’ [ 34 ]. Physician culture dictates that openly criticizing each other is to be avoided, whereas an open culture is needed to be able to discuss each other’s performance [ 35 ]. Studies of Witman [ 36 ] and Scheepers [ 37 ] in the Netherlands revealed flaws in the achievement of an open culture.…”
Section: Resultsmentioning
confidence: 99%
“…The RCN 16 advise practice on a manikin until competent and Shehab, 9 42 promotes a learning environment where staff are provided opportunities to discuss practice scenarios utilizing a problem-solving approach without fear of blame or repercussions and supervisors and leaders are supportive of the learning environment. 43 Peter et al, 7 Norman et al, 6 analysis and accountability at organizational board level. 44 However, CAUTI has the potential to develop into catheter associated blood stream infection (CABSI), accounting for 20% of all cases of E. coli bacteraemia.…”
Section: Discussionmentioning
confidence: 99%
“…Research by West et al 41 identified a relationship between the extent of in‐house education offered to staff and patient mortality, therefore it is imperative that education is prioritized. An open organizational culture, such as a just culture, 42 promotes a learning environment where staff are provided opportunities to discuss practice scenarios utilizing a problem‐solving approach without fear of blame or repercussions and supervisors and leaders are supportive of the learning environment 43 …”
Section: Discussionmentioning
confidence: 99%
“…The association between just culture and empathic and non-judgemental responses to PSIs has been clear 18 50 66 67. This is identified as a core condition for an open communication, and to establish positive relationships between peer supporters and HCWs, thereby enhancing programme adherence 67 68.…”
Section: Discussionmentioning
confidence: 99%
“…The association between just culture and empathic and non-judgemental responses to PSIs has been clear 18 50 66 67. This is identified as a core condition for an open communication, and to establish positive relationships between peer supporters and HCWs, thereby enhancing programme adherence 67 68. Namely, willingness to give support with empathy, leadership skills, reliability, being communicative and not being judgemental are essential elements for effective peer support 62.…”
Section: Discussionmentioning
confidence: 99%